Prevalence and Molecular Characterization of Microbial Contaminants in Raw Cow Milk of Tangail District in Bangladesh - Mahmud, Shahin; Ali, Md. F.; Faruque, Md. Omar; Wasim, Muhammad; Evamoni, Fatematuz Zuhura; Chowdhury, Kamal; Napis, Suhaimi; Mohiuddin, A.K.M. (Current Nutrition & Food Science, 2022)
Objectives: The aim of this study is to evaluate the microbial quality and associated health risk of raw milk from the Tangail region of Bangladesh. Methodology: An intensive study was carried out from January to October 2019 at the Tangail district of Bangladesh to assess bacterial contamination of raw milk. A total of 60 samples were examined by following the standard bacteriological methods and the health impact was evaluated with the help of a semi-structured-based questionnaire. Molecular characterization of isolated bacteria was carried out by PCR. Results: Results revealed the mean values of TVC and TCC in raw milk, udder, oil, and utensil samples were 7.6×106, 8.8×106, 4.6×106, and 1.3×106 cfu/ml and 3.7×105, 1.4×106, 4.4×105, and 8.9×104 cfu/ml, respectively. The yeast and mold in raw milk, udder, and oil were 1.5×103, 1.8×103, and 1.3×102cfu/ml, respectively, and the mean values of E. coli in the abovementioned samples were 1.9×103, 1.8×104, 2.1×103, and 1.6×103cfu/ml, respectively. On the other hand, the mean values of Salmonella spp. in raw milk, udder, oil, and utensil samples were 2.4×102, 7.9×102, 1.5×102, and 1.1×102cfu/ml, respectively. Some selected isolates confirmed by molecular identification were tested for their sensitivity against some common antibiotics used in Bangladesh. Escherichia coli showed 70% resistance to Amoxicillin and 90% sensitivity to Ciprofloxacin whereas Salmonella spp. and Staphylococcus aureus showed 90% resistance to Ampicillin and both were 80% and 90% sensitive to Ciprofloxacin, respectively Conclusion, Significance, and Impact of Study: Milk producers should be appropriately trained to monitor the overall hygienic conditions surrounding the production and handling of milk until it reaches the consumer. Frequent monitoring of the milk production facility, occasional testing of raw milk, and minimal use of antibiotics will ensure the quality of milk. Consumption of quality milk and avoidance of raw milk consumption will reduce the health risk of the consumers.
Keywords: antibiotic